Addition of hydrogen to gasoline-fuelled 4 stroke SI engine using 1-dimensional analysis - Mohd Aswad, Abd Wahab (2009)
This thesis was about simulation analysis on 4 stroke single cylinder engine by 1-Dimensional software. Objective of this thesis is to investigate the effect of NOx emission when hydrogen addition is added to the engine and relation between hydrogen addition and cylinder temperatures. Through these objectives, result of the project can obtain by using 1-Dimensional analysis software. GT-Power software is 1-Dimensional analysis software used in this project. GT-Power was used to develop a baseline design engine in order to do a simulation for 4 stroke single cylinder engine.Air-fuel ratios for hydrogen-gasoline mixture are calculated to get the stoichiometric for mixture. In this thesis, air-fuel ratio is used as parameters in GT-Power software. Default parameter in the GT-Power software was used as an engine parameter in this thesis. The ratio of hydrogen-gasoline fuel also must be change at SI-inject which is intake valve in GTPower software. With using default parameter from GT-Power software, a baseline design engine can be developed before run the simulations. After finish the simulation, the results are plotted by using Microsoft Excel. There are many result can be obtained by using GT-Power software but for this simulation, result of NOx emission and temperature are to be consider in this project. These 2 analyses were performed at 3 different engine speeds which are 1000 rpm, 3000 rpm and 5000 rpm, and at 10 until 20 air-fuel ratio. The result shown NOx emissions increased with the increase of hydrogen addition due to the raised cylinder temperature.